Global Geographic Differences in Healthcare Utilization for Sickle Cell Disease Pain Crises in the CASiRe Cohort - Strunk, Crawford; Tartaglione, Immacolata; Piccone, Connie M (Blood Cells Mol Dis, 2022)
BACKGROUND: Sickle cell disease (SCD) is characterized by frequent, unpredictable pain episodes and other vaso-occlusive crises (VOCs) leading to significant healthcare utilization. VOC frequency is often an endpoint in clinical trials investigating novel therapies for this devastating disease. PROCEDURE: The Consortium for the Advancement of Sickle Cell Research (CASiRe) is an international collaboration investigating clinical severity in SCD using a validated questionnaire and medical chart review standardized across four countries (United States, United Kingdom, Italy and Ghana). RESULTS: This study, focused on pain crisis incidence and healthcare utilization, included 868 patients, equally represented according to age and gender. HgbSS was the most common genotype. Patients from Ghana used the Emergency Room/Day Hospital for pain more frequently (annualized mean 2.01) than patients from other regions (annualized mean 1.56 U.S.;1.09 U.K.; 0.02 Italy), while U.K. patients were hospitalized for pain more often (annualized mean: U.K. 2.98) than patients in other regions (annualized mean 1.98 U.S.; 1.18 Ghana; Italy 0.54). Italy’s hospitalization rate for pain (annualized mean: 0.57) was nearly 20 times greater than its emergency room/day hospital only visits for pain (annualized mean: 0.03). When categorized by genotype and age, similar results were seen. CONCLUSIONS: Geographic differences in pain crisis frequency and healthcare utilization may correlate with variable organization of healthcare systems among countries and should be considered regarding trial design, endpoints, and analysis of results when investigating novel agents for clinical benefit.
Keywords: Connie M. Piccone; Raffaella Colombatti; Biree Andemariam; Sickle Cell disease; pain crisis; complications; geographic differences; health resources utilization; ACE: Genetic Medicine; WAGMC; University of Ghana